PENGARUH MOTIVASI BELAJAR DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR ALQURAN HADIS KELAS X MA AL MUHAJIRIN TUGUMULYO TA. 2017 – 2018 - Agus Wahyudin (IAIN Bengkulu, 2019)
The formula at the research is The Al Muhajirin Islamic Senior High School Tugumulyo is a education the swasta institute have the achievement to know from the statistic graudiantion data and change class is up. The beside at general lesson study, the islamic lesson studi have the same. But the special The Al Qur’an and Hadits, there are many student is low have Minimum Completion Criteria (KKM) subject is 75/76. The other indicator is low the learning motivation and the learning discipline is low, its can showed the habits at school, as didn’t to studying with maximal as the late came to class, dowsiness, and didn’t homework, didn’t active at class or group, the peformence student is hight and didn’t studying is special at Monday, made a scene in the class if the teacher was absen. The research uses a quantitative approach using associative methods. While this type of research is field research. The research data was collected using the observation method, questionnaires and documentation using multiple regression and F test. The results of the research that: 1) The results of the t test above can be explained that the Motivation variable towards learning outcomes at The Al Muhajirin Islamic Senior High School Village F Trikoyo, Tugumulyo Subdistrict, MusiRawas Regency showed that ttest = 3.471 was more than ttable = 1.683 with dk = 40 and significant level sig = 0.004, this means that partially the Motivation variable had a significant effect on learning outcomes at The Al Muhajirin Islamic Senior High School Village F Trikoyo District TugumulyoMusi Rawas Regency. This proves the hypothesis in the study is proven and the hypothesis is accepted. 2) The results of the t test are explained that the Discipline variable learns about the learning outcomes of the The Al Muhajirin Islamic Senior High School Village F Trikoyo, TugumulyoSubdistrict, MusiRawas Regency showed that tcount = 3.782 was greater than t table = 1.683 with dk = 40 and significant level sig = 0.001, this means that partially the discipline of learning discipline had a significant effect on learning outcomes at The Al Muhajirin Islamic Senior High School Village F Trikoyo District TugumulyoMusiRawas Regency. This proves the hypothesis in the study is proven and the hypothesis is accepted. 3) Value of Ftest > Ftable means that Ho is rejected and Ha is accepted, meaning the Motivation variable (X1) and learning Discipline variable (X2) have a significant effect on learning outcomes (Y) in The Al Muhajirin Islamic Senior High School Village F Trikoyo District Tugumulyo Musi Rawas Regency.